The Influence of Profitability, Solvency, and Liquidity on Stock Prices of Food and Beverage Subsector Companies Listed on the IDX - Christian Maranatha; Pujiarti Pujiarti (eCo-Buss, 2025)
Using purposive sampling, this study examines the partial and simultaneous effects of profitability, solvency, and liquidity on the stock prices of 6 food and beverage companies listed on the Indonesia Stock Exchange over a five-year period (2019-2023), resulting in 30 data points the model explains 64.5% of the stock price variance (Adjusted R Square = 0.645), and the remaining 35.5% is explained by other variables not modeled. Partial tests also show that profitability, especially return on assets, significantly affects stock prices, when liquidity is evaluated using the current ratio, it does not appear to influence stock prices, obtaining a t-value of 3.270 > 2.05553 from t-table and a significant value of sig. 0.003 < 0.05., Solvency, specifically measured by the debt-to-asset ratio, demonstrates a relationship with stock prices, obtaining a t-value of 2.513 > 2.05553 from t-table and a significant value of sig. 0.018 < 0.05., there is an no effect of liquidity as a current ratio on stock prices, obtaining a t-value of -0.038 < 2.05553 from t-table and a significant value of sig. 0.970 > 0.05. The combined effect of profitability (ROA), solvency (DAR), and liquidity (CR) on stock prices was found to be significant in a simultaneous test. This is shown by the results of the significance level of 0.001 < 0.05 and the Fcount value of 7.148 > 2.98 from Ftable.